PR- A Persuasive Industry? Spin, Public Relations and the Shaping of the Modern Media - Morris, T. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
Public relations is a big and rapidly growing industry, with annual growth rates of 20-30%. It spans the worlds of business, politics and culture, sport and entertainment. PR is everywhere. And yet, though it is much talked about it is little analyzed.